2021
DOI: 10.1101/2021.02.03.21251060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of early versus delayed rehabilitation following rotator cuff repair: systematic review and meta-analyses

Abstract: Objective: To investigate the effectiveness of early rehabilitation compared with delayed/standard rehabilitation after rotator cuff repair for pain, function, range of movement, strength, and repair integrity. Design: Systematic review and meta-analyses. Methods: We searched databases and included randomised controlled trials (RCTs) comparing early with delayed/standard rehabilitation for patients undergoing rotator cuff repair surgery. We assessed risk of bias of the RCTs using the Cochrane RoB 2 tool. R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…39,40,52 Other studies confirm that immediate range of motion exercises did not show any side effects in patients with rotator cuff repair, and the means of initiating a passive range of motion did not significantly affect the rate of tendon re-tear. [64][65][66][67] Early mobilization might also decrease the limitations and inconvenience caused by sling immobilization. 40 However, in patients with anatomic total shoulder arthroplasty, a higher degree of failure to heal the subscapularis was found in the immediate mobilization group.…”
Section: Discussionmentioning
confidence: 99%
“…39,40,52 Other studies confirm that immediate range of motion exercises did not show any side effects in patients with rotator cuff repair, and the means of initiating a passive range of motion did not significantly affect the rate of tendon re-tear. [64][65][66][67] Early mobilization might also decrease the limitations and inconvenience caused by sling immobilization. 40 However, in patients with anatomic total shoulder arthroplasty, a higher degree of failure to heal the subscapularis was found in the immediate mobilization group.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review suggested that early rehabilitation may be beneficial to patients with no additional risk imposed to the repair integrity. 8 However, only a minority of the RCTs that were included in the systematic review recruited patients with large tears. The RCT from Sheps, Silveira, 9 the largest completed to date ( n = 206), included patients with large tears in their sample.…”
Section: Discussionmentioning
confidence: 99%